Normal MR appearance of the pituitary gland in the first 2 years of life. - Dietrich, R B; Lis, L E; Greensite, F S; Pitt, D (American Journal of Neuroradiology, 1995)
PURPOSE To investigate changes in the size, shape, and signal intensity of the pituitary gland during the first 2 years of life. METHODS One hundred consecutive MR studies, spin-echo T1- and T2-weighted sequences, of children 0 to 2 years of age were analyzed. Signal intensity and shape of the gland were graded and its signal intensity measured. RESULTS There was a statistically significant difference in the signal intensity of both the anterior and posterior pituitary gland and in the shape between children younger than and older than 6 weeks of age and younger than and older than 27 weeks of age. There were definite trends in the size of the gland with age (decrease in height and increase in anteroposterior diameter and width). CONCLUSIONS There are changes in the pituitary gland in the newborn period that may reflect the ongoing changes in pituitary hormones reported to occur during this time.